Pengaruh Current Ratio, Debt To Equity Ratio Dan Price Book Value Terhadap Harga Saham Pada Sub Sektor Transportasi Yang Terdaftar Di BEI Periode 2012-2016 - Sri Anah; Iwan Firdaus; Erna Alliffah (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This research is to find out the influence of the current ratio, debt to equity ratio, and price book value on the stock price of companies listed in the Indonesia Stock Exchange transportation sub sector. The sample selection in this research using purposive sampling. The research data is obtained from Indonesia Stock Exchange. The method used in this research is panel data regression analysis and it is found that the more appropriate model used is random effect. From result of research got partially show that price book value variable have positive and significant effect to stock price. However, the partial current ratio variable have positive and no significant effect on the stock price and the variable of debt to equity ratio partially have negative and no significant effect on the stock price.